👤
a fost răspuns

(radical din 216-radical din 726): radical din 6-(radical din 486 - radical din 294): radical din 3=
Vă rog? ​


Răspuns :

Răspuns:

[tex](\sqrt{216} -\sqrt{726}): \sqrt{6} -(\sqrt{486} -\sqrt{294} ): \sqrt{3}=[/tex]

[tex]= (\sqrt{36*6} -\sqrt{121*6}): \sqrt{6} -(\sqrt{81*6} -\sqrt{49*6} ): \sqrt{3}=[/tex]

[tex]=(6\sqrt{6} -11\sqrt{6}): \sqrt{6} -(9\sqrt{6} -7\sqrt{6} ): \sqrt{3}=[/tex]

[tex]=-5\sqrt{6}:\sqrt{6} -2\sqrt{6}: \sqrt{3}=[/tex]

[tex]=-5 -2\sqrt{2*3}: \sqrt{3}=[/tex]

[tex]=-5 -2\sqrt{2}*\sqrt{3}: \sqrt{3}=[/tex]

[tex]=-5 -2\sqrt{2}[/tex]

Explicație pas cu pas: